Effectiveness of a five-component multimodal intervention on executive function in children with Autism spectrum disorder: A study protocol for a randomized controlled trial - Kazi Md Azman Hossain; Suraiya Yesmin Sharna; Farzana Sharmin; Tofajjal Hossain; Jahid Hasan Naim; Al Amin; Touhidul Islam Badhon (PLoS ONE, 2026)
Background Autism Spectrum Disorder (ASD) is characterized by persistent deficits in social interaction, communication, and executive functions such as inhibitory control, cognitive flexibility, and working memory. These deficits hinder daily functioning and learning outcomes in children. Exercise-based interventions improve executive function; however, most previous studies have focused on single-modality programs with limited generalizability. This trial aims to evaluate the effectiveness of a structured, five-component multimodal intervention—comprising yoga, aerobic, strengthening, neurocognitive, and music-based mindfulness activities—on improving executive functioning in children with ASD. Methods This assessor-blinded, double-center randomized controlled trial will enroll 130 children aged 4–18 years diagnosed with ASD in Bangladesh. Participants will be randomly assigned (1:1) to either the experimental group receiving the multimodal intervention or a wait-list control group receiving healthy lifestyle guidelines. The intervention will include five supervised sessions per week for 12 weeks, followed by a 12-week follow-up. An additional group of 65 typically developing children will serve as healthy controls. Primary outcomes will assess executive function domains: inhibitory control (Go/No-Go Task), cognitive flexibility (Trail Making Test A–B), and working memory (Corsi Block Tapping Task; Forward and Backward Digit Span). Secondary outcomes include social responsiveness (Social Responsiveness Scale–2) and ASD-related behaviors (Autism Treatment Evaluation Checklist). Outcomes will be evaluated at baseline, 12 weeks, and 24 weeks by blinded assessors. Data will be analyzed using SPSS following the intention-to-treat principle. Discussion This trial will address an important evidence gap by evaluating a comprehensive, low-cost, non-pharmacological multimodal intervention targeting multiple domains of executive function in children with ASD. The findings may help clinicians, educators, and policymakers adopt structured exercise-based programs within rehabilitation, school, and community settings. Although limited to two centers, the results could guide future large-scale studies and support the development of standardized multimodal intervention guidelines for ASD. Trial registration This trial is prospectively registered with the Clinical Trial Registry of India: CTRI/2025/11/096943 [Registered on: 06/11/2025]. Link: https://ctri.nic.in/Clinicaltrials/pmaindet2.php?EncHid=MTQ1NDEy&Enc=&userName=